FORMULASI DAN UJI TRANSPOR TRANSDERMAL IN-VITRO EMULSI KETOPROFEN MENGGUNAKAN HIDROKSIPROPIL METILSELULOSA SEBAGAI EMULGATOR - , Made Dwi Pradipta Wahyudi S., Dr. Akhmad Kharis Nugroho, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transdermal delivery system is one of the most promising delivery system to avoid the side effects of ketoprofen to our stomach. The purposes of this study were to make a homogeneous emulsion which is physically stable and to see the permeation profile of ketoprofen emulsion through skin. Emulsion formulas were determined by Design Expert 7.1.3. The evaluation of physical characteristics, viscosity, physical stability, and the release of ketoprofen were carried out to see the effect of combination. The physical stability assessment was determined by observing the separation fraction of emulsions in 35 days. The accelerated stability tests (i.e. centrifugation test and freeze-thaw study) were also carried out in this study. The cellophane membrane was used in drug release study as a separator between donor and acceptor compartment. The amount of drug that release from emulsions was determined for 4,5 hours. Transdermal permeation study was carried out on optimum formula using vertical diffusion cells for 10 hours. The results showed that the entire formulas produce a milky white homogeneous emulsion, with a characteristic odor and a pH of about 4. HPMC might give the greatest influence on the emulsion viscosity. In general, emulsion with highest viscosity has the best physical stability. Formulas that produce the most physically stable emulsion are formula 7 (HPMC 0.83%